Retrieval, caching, manipulation and visualization of GIS data in location aware applications - Nilsson, Magnus; Nilsson, Per (2002)
This thesis is made for the Alipes project. Alipes is a project at the Center for Distance-spanning Technology (CDT). CDT is a department at Luleå University of Technology. The purpose with this thesis is to investigate and evaluate a standard for transferring GIS data to a mobile user and to introduce a new map retrieval system for Location Aware Applications in the Alipes project. Also, a way to lower the cost related to map data, by introducing caching into the system, is investigated. An application that implements these areas has been created. There is a need for geographic information standards for all businesses that produces, distributes or utilizes spatial information. Since digital data from a wide variety of sources is used by a diversity of applications, a standard for transferring geographic information called Web Map Service (WMS) has been developed by the Open GIS Consortium (OGC). A problem with the currently net-based map retrieval is that it is very expensive and therefore prohibitive for usage in Location Aware Applications. That is: there is a need to reduce the number of request to the map server. A way to solve this problem is to use caching. Caching is a way to store and reuse data. There are different ways of caching data: the most common is to cache it locally (on disc) or to use a proxy server. An application that uses the WMS standard and caching is developed. It is implemented in a handheld computer (PDA), and retrieves its position and connects to the map server via WLAN. Using WMS also makes it possible to retrieve additional information about objects on the map, such as restaurants, movie theaters etc. The caching method used in the application is to download a larger map then the one requested. A smaller map is then cut out from the larger map and then used by the application. This way the client does not have to request the server for a new map unless the requested area is outside the downloaded map, hence the number of requests is reduced. Our conclusion is that the standardized ...